Genomic Simple Sequence Repeat Markers Reveal Patterns of Genetic Relatedness and Diversity in Sesame. Issue 2 (1st July 2015) - Uncu, Ayşe Özgür; Gultekin, Visam; Allmer, Jens; Frary, Anne; Doganlar, Sami
Abstract : Sesame ( Sesamum indicum L. syn. Sesamum orientale L.) is an orphan crop species with most molecular genetic research work done in the last decade. In this study, we used a pyrosequencing approach for the development of genomic simple‐sequence repeat (SSR) markers in sesame. Our approach proved successful in identifying 19, 816 nonredundant SSRs, 5727 of which were identified in a contig assembly that covers 19.29% of the sesame genome. Mononucleotide repeats were the most abundant SSR type identified in the sesame genome (48.5% of all SSRs), followed by dinucleotide SSRs (45.0%). Adenine–thymine‐rich motifs were predominant, representing 81.7, 51.7, 66.5, and 22.1% of the mononucleotide, dinucleotide, trinucleotide, and tetranucleotide SSRs, respectively. As a result of this work, we introduce 933 experimentally validated sesame specific markers, 849 of which are also applicable in Sesamum mulayanum (syn. Sesamum orientale var. malabaricum Nar.), the wild progenitor of cultivated sesame. Using a subset of the newly identified SSR markers, we analyzed molecular genetic diversity and population structure of a collection of world accessions. Results of the two analyses almost overlapped and suggested correlation between genetic similarity and geographical proximity. Indeed, a pattern of gene flow among sesame diversity centers was apparent, with levels of variability in some regions similar to that seen in the domestication origin of the crop. Taken together with the high rate of genomic marker transferability detected between S. indicum and S. mulayanum, our results represent additional molecular genetic evidence for designating the two taxa as cultivated and wild forms of the same species.